KEGIATAN SERVIS BERKALA DENGAN ASTRA HONDA MOTOR DI INSTITUT KEGURUAN DAN PENDIDIKAN (IKIP) PGRI KALIMANTAN TIMUR - Marbun, Samuel; Nurodanika, Mawarda; Indarto, Seto; Marthiani Siyadi, Henita; Almes Muntu, Yonathan (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The Periodic Service Activity with Astra Honda Motor conducted at IKIP PGRI Kalimantan Timur is a form of community service implementation and a reinforcement of collaboration between higher education institutions and the industrial sector. This activity aims to provide free motorcycle maintenance services for the academic community and to increase awareness and knowledge about proper motorcycle care among campus members. The implementation method consisted of three stages: (1) planning and coordination with Astra Honda and the local AHASS network, (2) carrying out the periodic motorcycle service, and (3) evaluating the activity. The results showed a high level of enthusiasm from the academic community. This program demonstrates that collaboration between universities and the industrial sector can provide tangible benefits for the campus community, while also serving as a practical learning opportunity for students. Such programs are expected to be conducted continuously to support skill development and strengthen community engagement within higher education institutions.